The Impact of Knowledge Trips through the Web Pages in the Teaching of Physics on the Achievement of Ninth Grade Students - Fathia Othman; Ahmed, Mohamed (Zenodo, 2023)
ABSTRACT This study was conducted on the impact of knowledge trips via the web in the teaching of physics on the achievement of 9th -grade students in terms of their level of remembering, understanding, and application. The study was applied to 62 9 th grade students from private schools in Libya, divided into experimental and control groups. It used a quasi-experimental method. To achieve the objectives of the study, the researcher pre- pared an achievement test in physics and a teachers guide as tools for collecting study data, and their validity and reliability were verified by appropriate methods. This study used the T-test for two independent groups to identify the differences between the ex- perimental and control groups and the ETA-Squared equation to measure the effect size. The statistical results of this practical study have demonstrated that there are dif- ferences between the means of the experimental and control groups in remembering, understanding, and application levels, and total scores in the direction of the experi- mental group, as well as total scores in the post-test for the experimental group in the achievement test for the light as a whole. The effect size ranges between the three lev- els and the effect of the total degree is large effect. Keywords: knowledge trips, web pages, teaching, physics achievement, Ninth-grade students, students remembering, students understanding and application.
Keywords: 4. Education; 3. Good health